A RARE CASE OF COEXISTING BLADDER SMALL CELL NEUROENDOCRINE CARCINOMA AND PROSTATE ADENOCARCINOMA: CASE REPORT AND LITERATURE REVIEW - Tania, Clarissa; Raja Pardamean Lumban Tobing, Edwin; Tansol, Christiano; Diana Prasetiyo, Patricia; Khairul Wallad, Caesar (Indonesian Urological Association, 2024)
Objective: We present a case of synchronous malignancies of rare bladder small cell neuroendocrine carcinoma (SCNC) and prostate adenocarcinoma and provide literature review of bladder SCNC. Case(s) presentation: A 72-year-old male smoker presented with 3 months history of gross hematuria. Ultrasonography showed a large hypoechoic mass in the right bladder. TURBT was performed and histopathology of the TURBT specimen showed a high-grade papillary urothelial carcinoma. Abdominal contrast-enhanced computed tomography (CECT) demonstrated an isodense heterogenous undefined mass, with irregular border at right anterolateral side of bladder wall. Radical cystoprostatectomy, bilateral radical lymph node dissection and bilateral ureterocutaneostomy was performed. Histopathology and immunohistochemical examination after radical cystoprostatectomy revealed bladder small cell neuroendocrine carcinoma coexisting with prostate adenocarcinoma (Gleason score 3+3=6, group 1). The patient eventually succumbed to disease after having symptomatic disease progression and metastatic disease five months after the surgery. Discussion: Bladder SCNC is a rare malignancy with an incidence of 1–9/1,000,000 reported. This tumor has an aggressive clinical course with high incidence of metastasis, and it tends to confer dismal prognosis. No specific clinical symptom exists. Histopathological recognition and immunohistochemistry is required to differentiate this rare entity. Conclusion: Clinicians and pathologists should be alert to the possibility of bladder SCNC despite extremely scarce incidence. Keywords: Bladder cancer, small cell neuroendocrine carcinoma, synchronous malignancy, case report.